(untitled) (Journal of International Crisis and Risk Communication Research, 2023)
Crisis communication scholars have suggested that sincerity is critical to an effective crisis response, and a robust body of research suggests that certain mannerisms and communication styles can make a spokesperson appear more sincere. But what impact do perceptions of a crisis communicator’s nonverbal sincerity and verbal honesty have in impacting the organization’s reputation and also consumer behavior? Grounded on the revised model of reputation repair (REMREP) which emphasizes an organization’s perceived virtuousness and a crisis’s perceived offensiveness, this paper reports a study in which participants (N = 785) watch an interview of a spokesperson representing a scandalized company. The results indicate that a spokesperson’s perceived sincerity has a small, structural effect on reputation and behavioral intentions. However, the effects largely result from increasing perceived honesty of the spokesperson’s response.This research has been conducted in compliance with the guidelines of the APA and under supervision of an IRB.